Organizational Performance: The Role of TQM Practices in Banking Sector of Pakistan - Nida Nazar; Sara Ravan Ramzani; Temoor Anjum; Imran Ahmed Shahzad (European Scientific Journal, ESJ, 2018)
The main purpose of this study was to investigate the m relationship between Total Quality Management (TQM) and Organizational Performance (OP). The motivation for this study was driven by the inconsistent findings in the literature concerning the relationships between TQM and OP. Due to the inconsistent results, a new research has emerged and this has prompted further investigation on the effects of other variables that may better explain the nature of these links. Questionnaires were distributed to 400 Sections of the Pakistani banks. 230 questionnaires were returned and used in the analysis using the PLS-SEM. The results of this study revealed that TQM is significant predictors of OP